1976
DOI: 10.1152/jappl.1976.40.1.74
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative description of normal AV nodal conduction curve in man

Abstract: The AV nodal conduction curve generated by the atrial extrastimulus technique has been described only qualitatively in man, making clinical comparison of known normal curves with those of suspected AV nodal dysfunction difficult. Also, the effects of physiological and pharmacological interventions have not been quantifiable. In 50 patients with normal AV conduction as defined by normal AH (less than 130 ms), normal AV nodal effective and functional refractory periods (less than 380 and less than 500 ms), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…[1][2][3] By plotting AV nodal resting intervals against the resultant AV nodal conduction time (AH interval), it is noticed that the latter is an exponential function of the former. [4][5][6][7] Although in children and young adults we found that there was an age dependent increase in the exponential time constant and the AV nodal effective refractory period (AVNERP), 8 in the older population this information was not available. The purpose of this study was to evaluate the effects of aging on these AV nodal recovery properties in the adults.…”
Section: Introductionmentioning
confidence: 86%
“…[1][2][3] By plotting AV nodal resting intervals against the resultant AV nodal conduction time (AH interval), it is noticed that the latter is an exponential function of the former. [4][5][6][7] Although in children and young adults we found that there was an age dependent increase in the exponential time constant and the AV nodal effective refractory period (AVNERP), 8 in the older population this information was not available. The purpose of this study was to evaluate the effects of aging on these AV nodal recovery properties in the adults.…”
Section: Introductionmentioning
confidence: 86%
“…However, if it modulates the PR interval, this interval will be changed in parallel with the PP interval [1,2]. On the other hand, an intrinsic mechanism that the AV node possesses affects AV conduction time, as opposed to an alteration in sinoatrial rhythm [3,4]. Therefore the intrinsic mechanism of the AV node, rather than the extrinsic vagal mechanism, can contribute to such compensatory modulation of the PR interval.…”
Section: The Variability Of Pr Interval During Dynamic Exercisementioning
confidence: 99%
“…On the other hand, an intrinsic mechanism that the AV node has affects AV conduction time as opposed to an alteration in sinoatrial rhythm. For example, when atrial pacing decreases cardiac cycle length, the AV interval lengthens [3,4,[8][9][10]. Neither the autonomic blockade nor cardiac denervation affects the response in AV conduction, supporting an intracardiac origin of the cycle length dependent effect [4,[8][9][10].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The mathematical formulation presented in equation 2.1 has been widely used as the basis for later works [66,67,68,69,70,71,72,73,74]. Although, in some other works, the usefulness of hyperbolic or pseudo-linear approximations has also been suggested [75,76].…”
Section: Models Of the Av Timementioning
confidence: 99%